The Efficacy and Safety of Wenxin Keli in Patients with Frequent Premature Ventricular Contractions: A Randomized, Double-blind, Placebo-controlled, Parallel-group, Multicenter Trial - Wei Hua; Run-Lin Gao; Bu-Chang Zhao; Jing Wang; Xu-Hua Chen; Chi Cai; Shu Zhang (Chinese Medical Journal, 2015)
Background: Premature ventricular contractions (PVCs) are common in the general population, and frequent PVCs may result in the poor quality of life or even the damage of cardiac function. We examined the efficacy and safety of a traditional Chinese medicine Wenxin Keli for the treatment of frequent PVCs among a relatively large Chinese cohort. Methods: We performed a randomized, double-blind, placebo-controlled, parallel-group, multicenter trial. A total of 1200 eligible participants were randomly assigned in a ratio of 1:1 to receive Wenxin Keli or the placebo for 4 weeks. The primary and secondary endpoint was the change of PVC numbers and PVC-related symptoms after a 4-week treatment compared with baseline, respectively. In addition, vital signs, laboratory values, and electrocardiographic parameters were assessed in a safety analysis. Results: At the initial evaluation, no significant differences in the baseline characteristics were observed between the Wenxin Keli group and the placebo group. A smaller number of PVCs was observed after the 4-week treatment than at baseline, in both the Wenxin Keli group (5686 ± 5940 vs. 15,138 ± 7597 beats/d, P < 0.001) and the placebo group (10,592 ± 8009 vs. 14,529 ± 5929 beats/d, P < 0.001); moreover, the Wenxin Keli group demonstrated a significantli greater reduction in the frequency of PVCs than the placebo group (P < 0.001). In a full analysis set, patients in the Wenxin Keli group exhibited significantly higher total effective responses in the reduction of PVCs compared to those in the placebo group (83.8% vs. 43.5%,P < 0.001). The per-protocol analysis yielded similar results (83.0% vs. 39.3%,P < 0.001). Treatment with Wenxin Keli also demonstrated superior performance compared to the placebo with respect to PVC-related symptoms. No severe adverse effects attributable to Wenxin Keli were reported. Conclusions: Wenxin Keli treatment effectively reduced the overall number of PVCs and alleviated PVC-related symptoms in patients without structural heart diseases and had no severe side effects.